Autism spectrum disorder in adults: diagnosis, management, and health services development - Murphy CM (Dove Medical Press, 2016)
Clodagh M Murphy,1,2 C Ellie Wilson,1–3 Dene M Robertson,1,2 Christine Ecker,1,4 Eileen M Daly,1,2 Neil Hammond,1,2 Anastasios Galanopoulos,1,2 Iulia Dud,1,2 Declan G Murphy,1,2 Grainne M McAlonan1,2 1Sackler Institute for Translational Neurodevelopment, Department of Forensic and Neurodevelopmental Sciences, King’s College London, Institute of Psychiatry, Psychology & Neuroscience, 2Behavioural and Developmental Psychiatry Clinical Academic Group, Behavioural Genetics Clinic, National Adult Autism Service, South London and Maudsley Foundation NHS Trust, London, UK; 3Individual Differences, Language and Cognition Lab, Department of Developmental and Educational Psychology, University of Seville, Spain; 4Department of Child and Adolescent Psychiatry, Psychosomatics and Psychotherapy, University Hospital, Goethe-University, Frankfurt am Main, Germany Abstract: Autism spectrum disorder (ASD) is a common neurodevelopmental disorder characterized by pervasive difficulties since early childhood across reciprocal social communication and restricted, repetitive interests and behaviors. Although early ASD research focused primarily on children, there is increasing recognition that ASD is a lifelong neurodevelopmental disorder. However, although health and education services for children with ASD are relatively well established, service provision for adults with ASD is in its infancy. There is a lack of health services research for adults with ASD, including identification of comorbid health difficulties, rigorous treatment trials (pharmacological and psychological), development of new pharmacotherapies, investigation of transition and aging across the lifespan, and consideration of sex differences and the views of people with ASD. This article reviews available evidence regarding the etiology, legislation, diagnosis, management, and service provision for adults with ASD and considers what is needed to support adults with ASD as they age. We conclude that health services research for adults with ASD is urgently warranted. In particular, research is required to better understand the needs of adults with ASD, including health, aging, service development, transition, treatment options across the lifespan, sex, and the views of people with ASD. Additionally, the outcomes of recent international legislative efforts to raise awareness of ASD and service provision for adults with ASD are to be determined. Future research is required to identify high-quality, evidence-based, and cost-effective models of care. Furthermore, future health services research is also required at the beginning and end of adulthood, including improved transition from youth to adult health care and increased understanding of aging and health in older adults with ASD. Keywords: autism, adults, diagnosis, management, service development